2013 IEEE International Conference on Computer Vision 2013
DOI: 10.1109/iccv.2013.129
|View full text |Cite
|
Sign up to set email alerts
|

Towards Motion Aware Light Field Video for Dynamic Scenes

Abstract: Current Light Field (LF) cameras offer fixed resolution in space, time and angle which is decided a-priori and is independent of the scene. These cameras either trade-off spatial resolution to capture single-shot LF [20,27,12]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Our work is closely related to the problem of projection matrix design in compressed sensing, where sparsity is used as a signal prior, and matrices are optimized in terms of properties such as incoherence or RIP [8,6]. Both sparsity [20,26] and PCA [2] signal priors have been used to design multiplexing matrices for compressive light field acquisition. Works such as this have demonstrated that data driven design can bring improvements to CI.…”
Section: Our Main Contributionmentioning
confidence: 99%
“…Our work is closely related to the problem of projection matrix design in compressed sensing, where sparsity is used as a signal prior, and matrices are optimized in terms of properties such as incoherence or RIP [8,6]. Both sparsity [20,26] and PCA [2] signal priors have been used to design multiplexing matrices for compressive light field acquisition. Works such as this have demonstrated that data driven design can bring improvements to CI.…”
Section: Our Main Contributionmentioning
confidence: 99%
“…CS relies on low-dimensional representations for the sensed signal such as sparsity under a transform or a dictionary. There is a rich body of work on applying CS to imaging of visual signals including images [25], [26] videos [10], [27], [28] and light fields [11], [29]. Most relevant to our paper is the video CS work of Hitomi et al [10] where a sparsifying dictionary is used on video patches to recover high-speed videos from low-frame rate sensors.…”
Section: G Compressive Sensing (Cs)mentioning
confidence: 99%
“…A second subset of such methods is programmable aperture imaging [6]. Compressive sensing and dictionary learning have also been applied to reduce the number of images required by exploiting the self-similarity among light field images [2], [21]. The Pelican imaging camera array [22] is a portable, practical light field capture system that can be implemented in a cellphone but has a limited angular range.…”
Section: Related Workmentioning
confidence: 99%